On Developing the Noise Reduction Model for Indonesian Aviation - Santoso Sukirno; Muhammad Suryanegara; Harry Sudibyo; Aprilia Sakti Kusumalestari (Institut Teknologi Bandung, 2019)
Aircraft noise exposure is still one of many abandoned pollution problems in Indonesia. The effects on human life have been studied more thoroughly in Europe and other regions. We review how some efforts have been implemented and how others must be further developed to support an integrated solution. Following several studies on noise exposure effects in Indonesia, future research must take part in reducing these effects. Indonesian research on noise reduction should follow the track of international research to develop sustainability and protect human capital. This paper reports the developing work aims for building a noise reduction model in the field of Indonesian aviation